2018
DOI: 10.1155/2018/3089317
|View full text |Cite
|
Sign up to set email alerts
|

The Constellation of Macrovascular Risk Factors in Early Onset T2DM: A Cross-Sectional Study in Xinjiang Province, China

Abstract: Background Despite a rapid popular of early onset type 2 diabetes (defined as diagnosis at <40 years old) recently, there is a lack of studies on this population in economically undeveloped area. We aimed to investigate the risk factors of macrovascular complications in the early onset T2DM patients in Xinjiang, China. Methods A cross-sectional survey of 1736 consecutive patients with T2DM was conducted. Macrovascular complications and risk factors were documented. Another nondiabetic population matched with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, a study from Xinjiang, China, showed that the late onset T2D patients had a glycemic control rate of 23.1%, while the early onset T2D patients had a glycemic control rate of only 14.2%. Moreover, both patients had lipid control rates of less than 10% [ 20 ]. The patients with T2D from nine European countries had a glycemic control rate of only 37.4% [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study from Xinjiang, China, showed that the late onset T2D patients had a glycemic control rate of 23.1%, while the early onset T2D patients had a glycemic control rate of only 14.2%. Moreover, both patients had lipid control rates of less than 10% [ 20 ]. The patients with T2D from nine European countries had a glycemic control rate of only 37.4% [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…As age and hyperglycemia duration increase, blood glucose worsens, and diabetic complications increase. Increasing evidence shows that T2DM is associated with cognitive impairment and dementia, and many epidemiological studies have shown that patients with T2DM have a significantly higher risk of developing AD [ 1 , 15 ]. The mechanism by which T2DM causes neurodegenerative diseases remains unclear and no drugs effectively prevent or delay disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the number of patients undergoing PCI is significantly increased, the length of hospital stay is increased, and the total hospitalization expenses are significantly increased. 19,20 With advancements in vascular access technology, scaffolding technology, and antiplatelet pharmacology, the discharge time after PCI has been greatly reduced. 21 Multiple clinical studies have demonstrated the safety of early and day-to-date discharge in patients with selective PCI, [22][23][24][25] and this strategy was deemed acceptable in the 2018 SCAI Expert Consensus Document on Hospitalization Time after Percutaneous Coronary Intervention (PCI) Promotion; 26 furthermore, this strategy prevents unnecessary hospitalization and is thus cost-effective for the Chinese healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the number of patients undergoing PCI is significantly increased, the length of hospital stay is increased, and the total hospitalization expenses are significantly increased. 19,20…”
Section: Discussionmentioning
confidence: 99%